PERTIMBANGAN HAKIM DALAM PENJATUHAN HUKUMAN KEPADA KORBAN PEMBUNUHAN DITINJAU DARI ASPEK KEADILAN HUKUM - Sesilia Selnika Wau (LPPM Universitas Nias Raya, 2025)
The aim of this research is to find out the judge's considerations in sentencing murder victims from the aspect of legal justice. The type of research used by the author is normative legal research using the Legislative Regulations approach, case method, analytical approach. Normative law is a type of legal research that places law as a system that studies and uses secondary data. Data collection was carried out using secondary data, which was obtained through library materials consisting of primary legal materials and secondary legal materials. The data analysis used is descriptive qualitative analysis and conclusions are drawn using a deductive method. Based on the research findings and discussion, it can be concluded that in his consideration the judge was negligent and/or did not take into account the interests of the victim in implementing legal justice, in this decision using Article 351 paragraph (1) in conjunction with Article 55 paragraph (1) of the Criminal Code that if violence This causes abuse which results in death with a maximum prison sentence of 7 (seven) years. However, according to the author's analysis, if we look at the chronology, there is an element of planning.